Weekly high-dose 5-fluorouracil as 24-hour infusion combined with sodium folinic acid (AIO regimen) plus irinotecan in second-line and sequential therapy of metastatic colorectal cancer (CRC) - Wein, Axel; Merx, Kirsten; Hofheinz, Ralf-Dieter (Anticancer research, 2017)
Background/Aim: The aim of this work was to evaluate the efficacy and safety of second-line treatment with weekly high-dose 5-fluorouracil (5-FU) as a 24-hour infusion (24-h inf.) combined with sodium folinic acid (FA) (AIO-regimen) plus irinotecan (Iri.) after pretreatment with AIO-regimen plus oxaliplatin (L-OHP). Patients and Methods: Patients with non-resectable distant CRC metastases were enrolled in a prospective phase II study for palliative second-line treatment after previous progression of first-line treatment in accordance with the AIO-regimen plus oxaliplatin. On an outpatient basis, the patients received a treatment regimen comprising of weekly 80 mg/m2 irinotecan in the form of a 1-hour i.v. infusion and 2,000 mg/m2 5-FU combined with 500 mg/m2 sodium folinic acid administered as a 24-h infusion i.v. once weekly. Results: During second-line treatment, a total of 59 patients received 520 chemotherapy applications. As the main higher-grade symptom of toxicity, diarrhea (NCI-CTC-toxicity grade 3) presented in 8 patients (13.6%, 95%CI=5.1-23.7), followed by leukocytopenia (CTC grade 3) in 3 patients (5.1%, 95%CI=0-11.9), followed by thrombocytopenia (CTC grade 3) in 1 patient (1.7%, 95%CI=0-5.1). Fifty-nine patients were evaluable for treatment response. The remission data can be summarized as follows: complete remission (CR); n=0; partial remission (PR); n=6 (10%; 95%CI=3.4-18.6); stable disease (SD); n=31 (53%; 95%CI=39.0-64.4); progressive disease (PD); n=19 (33%; 95%CI=20.3-44.1). The median progression-free survival (PFS) rate (n=59) was 4.2 months (range=3.8-5.8 months). The median survival time counted from the start of second-line treatment (n=59) 14.2 months (range 8.2-17.3 months) and the median survival time counted from the start of first-line therapy (n=59) 25 months (range 19-27 months). Conclusion: Palliative second-line treatment according to the AIO regimen plus irinotecan offers both a favourable toxicity profile and promising efficacy in second-line and palliative sequential therapy.
Gesehen am 30.10.2018